Praktykować media/Praktykować siebie… O doświadczaniu przestrzeni późnej nowoczesności - Banaszkiewicz, Karina (Załącznik Kulturoznawczy, 2021)
In advanced globalization, the digital code, computer, and Internet become tools of cultural change. 2-3-4.0 generation media produce images, artificial events, objects, as well as methods of vision prevailing in design, design processes, and communication. The number of visibility types offered to users, results in media matrices becoming regimes of (for) the eye, of (for) a bodily experience. It also shapes a sense of reality by means of media space (TV stream, cyberspace) and spaces inscribed in media forms (simulations, hybrids, onto-ontological topias). Two issues seem of particular relevance here. Questions about access to reality offered by ‘images’ (satellites, HDMI helmets, combat glasses, etc.) and possibilities of seeing the world from behind the visual media matrices. Media, multi-media communication platforms distribute not only schemes of viewing, but also the right to look (extranet, friends lists, access to archives and libraries, consumer profiles collected by Google, MS, etc.). The excess of artificial forms and spaces, on the other hand, directs attention to participation and participants of culture: individuals and communities (real, imagined, virtual). Their activities in cyberspace, including identity and identity practices, should be the focus of interest. The author of the text reflects upon identity practices of the individual, that is the individual’s participation in culture through the prism of immaterial materiality, self-care, and the need for bonds and integration with the Others. She discusses techniques of advanced audio-vision (their matrices and spatiality), as well as creation of subjective coherence negotiated with others in terms of individual – group (conventional) – universal content (e.g. humanity). Identity practices are located within the framework of data flows and transmissions, information bubbles, heterotopia, and identities of legitimization, resistance, and design implemented there. The author of the text also perceives identity from the perspective of a person and a mask, of users’ tactics articulating their presence in cyber-virtual communities (e.g. avatars, nicks, multiple identities), as well as in the perspective of data visualization: user profiles, metric identifiers, files, selection algorithms, search history, archives of published photos…, in other words – institutional (cyber)surveillance strategies.